Efficient Real-Time Digital Subcarrier Cross-Connect (DSXC) Based on Distributed Arithmetic DSP Algorithm - Xu, Tong; Fumagalli, Andrea; Hui, Rongqing (Journal of lightwave technology, 2020)
Two real-time functions of digital subcarrier cross-connect (DSXC) are experimentally demonstrated for the first time using distributed arithmetic (DA) in a field programmable gate array (FPGA) platform. Both frequency translation and channel selection in DSXC are implemented using DA-based resampling filters, achieving flexible modulation format and fine data-rate granularity of many concurrent subcarrier channels. Compared with traditional resampling filters that leverage multipliers, the DA-based approach eliminates the need for DSP slices in the FPGA implementation and significantly reduces the hardware cost. By requiring only a few clock periods, the DA-based resampling filter is also significantly faster when compared to conventional FIR filters, whose overall latency is proportional to the filter order. The DA-based DSXC is therefore able to achieve improved spectral efficiency and programmability of multiple orthogonal subcarrier channels, while keeping low cross-connection latency and requiring low cost hardware resources when implemented in a FPGA platform.